Penyuluhan Pedoman Umum Ejaan Bahasa Indonesia (PUEBI) kepada Guru di Sekolah SMP dan SMK IT Rahmatuttoyibah Aliflahah Kecamatan Gunung Kaler Kabupaten Tangerang - Chairunnisa (Medan Resource Center, 2022)
Because native Indonesian speakers struggle to use their language accurately and properly, this counseling exercise was conducted. Not only do students, lay speakers, or pupils exhibit this lack of proficiency, but also teachers. This kind of reality also exists in government institutions, which need to be the cornerstone of demonstrating proper and appropriate Indonesian usage. The languages used in various media spaces demonstrate this fact. When in reality the contrary is true, these native speakers frequently believe what they are doing to be morally correct. They frequently adhere to societal norms and emotional standards. This should be avoided since writing in Indonesian must comply to strict rules in order to maintain consistency. Based on these issues, this outreach effort was conducted to address the language issue in outdoor media. Given that teachers are subjects who serve as examples and role models for pupils and society, they are the ideal target object. As concrete proof that good and accurate Indonesian is prioritized, this activity takes the shape of material provision, debate, practice, and practical application. The target objects will ultimately be able to employ good and accurate Indonesian in outdoor media thanks to this service activity.